Posterior Sheath Block Versus Transversus Abdominis Plane Block In Abdominal Surgeries - Usman, Aleena; Ishrat, Zahra; Mahmood, Tariq; Ahmad, Chaudhary Adeel; Mueen, Burhan (Biological and Clinical Sciences Research Journal, 2025)
Effective postoperative pain management is a critical component of enhanced recovery protocols after abdominal surgery. Regional blocks, such as the posterior sheath (rectus sheath, RS) block and the transversus abdominis plane (TAP) block, are increasingly used to minimize opioid consumption and improve patient outcomes. However, evidence comparing their analgesic efficacy remains limited, particularly in resource-constrained settings such as Pakistan. Objective: To compare the analgesic efficacy of ultrasound-guided posterior sheath block and transversus abdominis plane block in patients undergoing abdominal surgery. Methods: This randomized controlled trial was conducted at the Department of Anesthesia, King Edward Medical University/Mayo Hospital, Lahore, between January and April 2025. Eighty patients aged 18–60 years with ASA I–II status scheduled for elective abdominal surgery were randomized into two groups: Group A (RS block, n=40) and Group B (TAP block, n=40). Both groups received 20 ml of 0.25% bupivacaine per block and local wound infiltration at the end of surgery. Postoperative pain was assessed at six hours using a 10-point visual analogue scale (VAS). Data were analyzed using SPSS 26.0, with p<0.05 considered statistically significant. Results: Baseline demographics, BMI, ASA status, and surgical procedures were comparable between groups (p>0.05). At six hours, mean VAS scores were significantly lower in the TAP group compared to the RS group (2.6 ± 0.8 vs. 4.5 ± 1.1; mean difference −1.9, 95% CI −2.32 to −1.48; p<0.001). Clinically significant pain (VAS >3) was present in 75% of RS block patients versus 20% of TAP block patients (risk difference −55.0%, 95% CI −71.3% to −38.7%; p<0.001). Subgroup analysis confirmed consistent superiority of TAP block across age, gender, BMI, and ASA categories (all p<0.05). Conclusion: The TAP block provided significantly superior postoperative analgesia compared to the RS block in patients undergoing abdominal surgery. These findings support the integration of TAP block into multimodal analgesia protocols to improve postoperative outcomes, particularly in healthcare systems with limited resources.